Attempting to counteract vigilance decrement in older adults with brain stimulation - Löffler, Birte S.; Stecher, Heiko I.; Meiser, Arnd; Fudickar, Sebastian; Hein, Andreas; Herrmann, Christoph S. (Frontiers in Neuroergonomics, 2023)
Introduction: Against the background of demographic change and the need for enhancement techniques for an aging society, we set out to repeat a study that utilized 40 Hz transcranial alternating current stimulation (tACS) to counteract the slowdown of reaction times in a vigilance experiment, but with participants aged 65 years and above. On an oscillatory level, vigilance decrement is linked to rising occipital alpha power which has been shown to be able to downregulated using gamma-tACS.Method: We applied tACS on the visual cortex and compared reaction times, error rates, and alpha power of a group stimulated with 40 Hz to a sham and a 5 Hz stimulated control group. All groups executed two 30-minute long blocks of a visual task and were stimulated according to group in the second block. We hypothesized that the expected increase in reaction times and alpha power will be reduced in the 40 Hz compared to the control groups in the second block (INTERVENTION).Results: Statistical analysis with linear mixed models showed that reaction times increased significantly over time in the first block (BASELINE) with approx. 3 ms/min for the SHAM-and 2 ms/min for the 5 Hz-and 40 Hz-group with no difference between the groups. The increase was less pronounced in the INTERVENTION-block (1 ms/min for SHAM-and 5 Hz, 3 ms/min for the 40 Hzgroup). Differences among groups in the INTERVENTION-block were not significant, if the 5 Hz or 40 Hz-group was used as the base-group for the linear mixed model. Statistical analysis with a 2 This is a provisional file, not the final typeset article generalized linear mixed model showed that alpha power was significantly higher after the experiment (1.37 µV²) compared to before (1µV²). No influence of stimulation (40 Hz, 5 Hz or sham) could be detected.Discussion: Although literature has shown that tACS offers potential for older adults, our results indicate, that findings from general studies cannot simply be transferred to an old-aged group. We suggest adjusting stimulation parameters to the neurophysiological features expected in this group. Next to heterogeneity and cognitive fitness, the influence of motivation and medication should be considered.